Entrepreneurship Financing Strategy for Early Childhood Education - Kusuma, Andi; Ubaidillah, Khasan (ABNA : Journal of Islamic Early Childhood Education, 2024)
The limited number of students and the socio-economic status of their parents, who fall into the lower middle class, result in PGRI Widya Loka Pujodadi kindergarten having insufficient financial resources. This study aims to investigate the management of financing for early childhood education at PGRI Widya Loka Pujodadi kindergarten, with a specific focus on entrepreneurship approaches. This research employs a qualitative descriptive method, focusing on the institution's financial staff as the main subject. The informants for this study include teachers, education staff members, committees, and Pujodadi village officials. The methodologies employed for data collection in this study encompass observation, interviews, and documentation. In order to ascertain the reliability of the research data, the researchers applied source and method triangulation. The data analysis technique used is an interactive analysis model. The research findings indicate that implementation management at institutions involves all institution components, ranging from teachers to parents of students. The institution's funding is derived from government allocations (BOS funds), parents' contributions, and internal entrepreneurial initiatives. Entrepreneurship can be fostered by institutions that provide financial support, enhance public accessibility, and cultivate relationships with the community and neighboring institutions. The formulation of financing at the institution is looked at based on a priority scale and guided by the institution's vision, mission, and goals.